Cross Polarization Minimized Fractal Antenna for HiperLAN Application - Sanish V. S. (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Two Fractal based antennas are proposed here for HiperLAN applications. Cantor Square fractal antenna has a size of 30mm×20mm×1.6mm and Sierpinski Carpet antenna has a size of 30mm×25mm×1.6mm. To reduce Cross polarization stubs have been introduced in the feed line and thereby achieving polarization purity for the above said antennas. Both antennas can resonate at a 5GHz band with good return loss and low cross-polarization. Cantor fractal and Sierpinski Carpet at its 2nd iteration gives up to -60dB cross polarization with a return loss at -35dB making these designs good for LAN applications